Development of an Accessible and Scalable Quantitative Polymerase Chain Reaction Assay for Monkeypox Virus Detection. (12th October 2022) - Porzucek, Abigail J; Proctor, Abigale M; Klinkhammer, Katharina E; Tritsch, Sarah R; Robertson, Molly A; Bashor, Jonathan P; Villani, Jack; Sepulveda, Jorge L; Mores, Christopher N
Abstract: During the 2022 monkeypox (MPX) outbreak, testing has been limited and results delayed, allowing ongoing transmission. Gold-standard quantitative polymerase chain reaction (qPCR) diagnostics are difficult to obtain. This research adapted the June 2022 CDC MPX qPCR assay for broad implementation. Validated using MPX stocks in a matrix with multiple sample types, MPX was detected with cycle threshold (Ct) values 17.46–35.59 and titer equivalents 8.01 × 10 6 to 2.45 × 10 0 plaque–forming unit (PFU)/mL. The detection limit was 3.59 PFU/mL. Sensitivity and specificity were both 100%. This qPCR assay can be quickly and broadly implemented in research and public health laboratories to increase diagnostic capacity amid the growing MPX outbreak. Abstract : Due to difficulty obtaining gold-standard qPCR diagnostics, this research adapted and validated the 2022 CDC monkeypox qPCR assay. This assay can be quickly and broadly implemented in research and public health laboratories to increase diagnostic capacity amid the growing outbreak. During the 2022 monkeypox (MPX) outbreak, testing has been limited and results delayed, allowing ongoing transmission. Gold-standard quantitative polymerase chain reaction (qPCR) diagnostics are difficult to obtain. This research adapted the June 2022 CDC MPX qPCR assay for broad implementation. Validated using MPX stocks in a matrix with multiple sample types, MPX was detected with Cq values 17.46–35.59 and titer equivalents 8.01 × 10 6 to 2.45 × 10 0 plaque-forming unit (PFU)/mL. The detection limit was 3.59 PFU/mL. Sensitivity and specificity were both 100%. This qPCR assay can be quickly and broadly implemented in research and public health laboratories to increase diagnostic capacity amid the growing MPX outbreak.